Bukti Histologis Peningkatan Imunitas Humoral akibat Pemberian Formulasi Poliherbal pada Hewan Model Imunogenisitas - Widhowati Supardi; Woro Rukmi Pratiwi; Juliana Irem Adriana Purukan; Eti Nurwening Sholikhah; Setyo Purwono (Alma Ata University Press, 2026)
Background: Antibiotic resistance (AMR) is a critical global health threat often exacerbated by inappropriate self-medication. In Indonesia, infectious diseases remain a leading cause of mortality, yet public understanding and practices regarding antibiotic use are often suboptimal. Objective: This study investigated the association between sociodemographic factors and the knowledge, beliefs, attitudes, and practices (KAP) regarding antibiotic use among the community in Bandar Lampung, Indonesia. Methods: A community-based cross- sectional survey was conducted from March to April 2023 across 31 primary healthcare centers in 17 sub- districts. A total of 418 respondents were selected using a two-stage cluster sampling method. Data were collected via a validated questionnaire (Cronbach’s Alpha > 0.6) and analyzed using Chi-square and Fisher’s exact tests (p<0.05). Results: The findings revealed that 53.35% of respondents possessed inadequate knowledge, while 49.76% practiced self-medication. Although 94.50% exhibited favorable attitudes toward rational use, a notable